Diaphragm, preparation method of polymer nanosheet, battery and energy storage device
By introducing a polymer functional layer into the lithium-ion battery separator, the nanomaterial formed by coordination between metal ions and organic ligands is solved, and the goal of improving battery energy efficiency and safety performance is achieved.
Patent Information
- Application Number
- CN202411723653.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
AI Technical Summary
The ceramic coating thickness of the existing lithium-ion battery separator is relatively large, resulting in a decrease in breathability and affecting energy efficiency. At the same time, reducing the thickness of the ceramic coating to improve breathability will damage the protective effect of the separator and affect the safety performance of the battery.
A separator including a base film and a polymer functional layer is used. The polymer functional layer is composed of a sheet-shaped nanomaterial with ordered pores formed by coordinated metal ions and organic ligands. The thermal decomposition temperature of the polymer nanosheets is between 400°C and 550°C, which improves the ionic conductivity and high temperature resistance of the separator.
It improves the energy efficiency and safety performance of lithium-ion batteries, extends the battery life, and enhances the high temperature resistance of the diaphragm.
Smart Images

Figure CN119601901A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a diaphragm, a method for preparing a polymer nanosheet, a battery, and an energy storage device. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) are usually composed of a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive and negative electrodes and prevent the two electrodes from contacting and short-circuiting.
[0003] In the related art, a ceramic coating is provided on the surface of the diaphragm substrate to protect the diaphragm substrate. However, in order to meet the protective effect of the diaphragm substrate, the conventional ceramic coating is relatively thick, which leads to a decrease in the air permeability of the diaphragm, affects the ionic conductivity of the diaphragm, and further affects the energy efficiency of the secondary battery; and if the air permeability is improved by simply reducing the thickness of the ceramic coating, the protective effect of the diaphragm will be deteriorated, and the diaphragm is prone to failure at high temperature, affecting the safety performance of the secondary battery. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a diaphragm, a method for preparing a polymer nanosheet, a battery and an energy storage device, which improve the energy efficiency of the secondary battery while improving the safety performance of the secondary battery.
[0005] In the first aspect, the present application provides a diaphragm, comprising: a base film and a polymer functional layer, wherein the polymer functional layer is arranged on at least one side surface of the base film; the polymer functional layer comprises polymer nanosheets, wherein the polymer nanosheets are sheet-like nanomaterials with ordered pores formed by the coordination of metal ions M and organic ligands; the thermal decomposition temperature of the polymer nanosheets is 400°C to 550°C.
[0006] In some embodiments of the present application, the thickness of the polymer functional layer is 1 μm to 2 μm.
[0007] In some embodiments of the present application, the average thickness of the polymer nanosheet is H, the average width of the polymer nanosheet is W, 50 nm≤H≤200 nm, 0.3 μm≤W≤1 μm.
[0008] In some embodiments of the present application, the pore size of the ordered pores in the polymer nanosheet is d, 5nm≤d≤50nm.
[0009] In some embodiments of the present application, the specific surface area of the polymer nanosheet is BET, 200m 2 / g≤BET≤1100m 2 / g.
[0010] In some embodiments of the present application, after the polymer nanosheets are immersed in the electrolyte for 500 hours, the total concentration of metal ions M in the electrolyte is less than 0.1 ppm.
[0011] In some embodiments of the present application, the diaphragm satisfies at least one of the following features:
[0012] a) the porosity of the diaphragm is 40% to 70%;
[0013] b) the air permeability of the diaphragm at 25° C. is 100 s / 100 cc to 200 s / 100 cc;
[0014] c) the thermal shrinkage of the diaphragm at 130° C. is less than or equal to 1.0%;
[0015] d) The thermal shrinkage rate of the separator at 150° C. is less than or equal to 1.4%.
[0016] In some embodiments of the present application, the metal ion M includes at least one of a zirconium ion, an aluminum ion, a calcium ion and a titanium ion, and the organic ligand includes at least one of diphenyl dicarboxylic acid, trimesic acid, 1,3,5-tri(4-carboxyphenyl)benzene, 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene, 1,3,5-tri(3,5-dicarboxylate-p-biphenyl)benzene and 1,3,5-tri(4-carboxyphenylethynyl)benzene.
[0017] In a second aspect, the present application provides a method for preparing a polymer nanosheet, comprising the following steps:
[0018] dissolving an organic ligand and a metal salt containing a metal ion M in a solvent to obtain a first solution;
[0019] Adding formic acid and water to the first solution, and mixing to form a second solution, wherein the concentration of formic acid in the second solution is 1.5wt% to 2.5wt%, and the concentration of water in the second solution is 0.3wt% to 0.8wt%;
[0020] The second solution is heated, and after the reaction is completed, the white solid precipitate generated by the reaction is filtered and collected to obtain the polymer nanosheet.
[0021] In some embodiments of the present application, the heating temperature is 115° C. to 125° C., and the heating time is 40 h to 60 h.
[0022] In some embodiments of the present application, the organic ligand is selected from at least one of diphenyl dicarboxylic acid, trimesic acid, 1,3,5-tri(4-carboxyphenyl)benzene (i.e., H3BTB) and 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene (i.e., TCBPB), 1,3,5-tri(3,5-dicarboxylate-p-biphenyl)benzene and 1,3,5-tri(4-carboxyphenylethynyl)benzene (i.e., H3BTE), and the metal salt is selected from at least one of zirconium chloride, aluminum chloride and calcium chloride.
[0023] In a third aspect, the present application provides a battery, comprising the separator described in the first aspect.
[0024] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the third aspect, wherein the battery is accommodated in the housing.
[0025] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.
[0026] Compared with the prior art, this application has at least the following beneficial effects:
[0027] The present application provides a diaphragm, a method for preparing a polymer nanosheet, a battery and an energy storage device, wherein the diaphragm includes a base film and a polymer functional layer, the polymer functional layer is disposed on at least one side of the base film; the polymer functional layer includes a polymer nanosheet, the polymer nanosheet is a sheet-like nanomaterial with ordered pores formed by the coordination of metal ions M and organic ligands; the thermal decomposition temperature of the polymer nanosheet is 400°C to 550°C. The polymer functional layer of the present application can improve the ionic conductivity and high temperature resistance of the diaphragm, so that the diaphragm with the polymer functional layer of the present application can improve the energy efficiency of the secondary battery while improving the safety performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application;
[0030] Figure 2 A schematic diagram of the structure of a diaphragm according to another embodiment of the present application;
[0031] Figure 3A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;
[0032] Figure 4 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;
[0033] Figure 5 This is a scanning electron microscope (SEM) image of the polymer nanosheet prepared in Example 1 of the present application.
[0034] Explanation of the reference numerals: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-base film, 20-polymer functional layer, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0036] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0037] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0038] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0039] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0040] It should be noted that, in the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0041] The present application provides a diaphragm, such as Figure 1 As shown, it includes a base film 10 and a polymer functional layer 20, and the polymer functional layer 20 is disposed on at least one side of the base film 10. In one embodiment, the polymer functional layer 20 is disposed on the side of the base film 10 facing the positive electrode plate; in another embodiment, the polymer functional layer 20 is disposed on the side of the base film 10 facing the negative electrode plate; in yet another embodiment, Figure 2 As shown, the polymer functional layer 20 is disposed on both sides of the base film 10, and the two sides of the base film 10 face the positive electrode sheet and the negative electrode sheet respectively.
[0042] The polymer functional layer includes polymer nanosheets, which are sheet-like nanomaterials with ordered pores formed by coordination of metal ions M and organic ligands; the thermal decomposition temperature of the polymer nanosheets is 400°C to 550°C; in another optional embodiment, the thermal decomposition temperature of the polymer nanosheets is 440°C to 530°C. For example, the thermal decomposition temperature is 400°C, 450°C, 500°C or 550°C.
[0043] The polymer functional layer of the present application is conducive to improving the ionic conductivity and high temperature resistance of the diaphragm, thereby improving the energy efficiency of the lithium-ion battery while improving the safety performance of the lithium-ion battery. This may be due to the following reasons: first, the polymer nanosheets have a two-dimensional sheet morphology and an ordered pore structure. Under the combined effect of the sheet morphology and the ordered pore structure, it is not only conducive to improving the air permeability of the polymer functional layer, but also enables the polymer functional layer to more fully absorb the electrolyte, improve the electrolyte retention capacity, and thus improve the ionic conductivity of the diaphragm; secondly, the thermal decomposition temperature of the polymer nanosheets in the polymer functional layer is high, which is conducive to improving the heat resistance of the polymer functional layer, thereby improving the high temperature resistance of the diaphragm; thirdly, the ordered pore structure in the polymer nanosheets can also adsorb impurities generated and dissolved in the electrolyte during the cycle of the lithium-ion battery, and the adsorbed impurities include but are not limited to Fe 2+ , Fe 3+ , Mn 2+ , Cu 2+ 、Zn 2+ 、Co 2+PO4 3- Since these impurities may produce side reactions with the electrolyte and consume the electrolyte, they can slow down the attenuation of lithium-ion batteries after being adsorbed. In summary, the separator with the polymer functional layer of the present application improves the energy efficiency of lithium-ion batteries while improving the safety performance of lithium-ion batteries, and is also conducive to extending the life of lithium-ion batteries.
[0044] In an optional embodiment, the thickness of the polymer functional layer is 1 μm to 2 μm, for example, the thickness of the polymer functional layer is 1 μm, 1.2 μm, 1.5 μm or 2 μm. By controlling the thickness of the polymer functional layer within the above range, on the one hand, it is helpful to ensure the high temperature resistance of the diaphragm, and on the other hand, it is helpful to improve the air permeability of the polymer functional layer, thereby improving the safety performance of the lithium-ion battery while improving its energy efficiency.
[0045] In an optional embodiment, the average thickness of the polymer nanosheet is H, the average width of the polymer nanosheet is W, 50nm≤H≤200nm, 300nm≤W<1000nm. For example, H is 50nm, 100nm, 150nm or 200nm, and W is 300nm, 500nm, 700nm or 950nm. The average thickness and / or average width of the polymer nanosheet is within the above range, the polymer nanosheet has a nanoscale size, presents a two-dimensional sheet morphology and has abundant nanopores. Compared with ordinary granular ceramic materials (such as aluminum oxide), this sheet-like nanomaterial is beneficial to reduce its thickness while ensuring the strength of the polymer coating, thereby facilitating the improvement of the membrane permeability and the electrolyte retention capacity.
[0046] In the present application, the average thickness of the polymer nanosheet refers to the thickness of 10 polymer nanosheets within the field of view under SEM, and then the average value is calculated; the average width of the polymer nanosheet refers to the size of the widest part of the 10 polymer nanosheets within the field of view under SEM, and then the average value is calculated.
[0047] In an optional embodiment, the pore size of the ordered pores in the polymer nanosheet is d, 5nm≤d≤50nm. For example, d is 5nm, 10nm, 20nm, 30nm or 50nm. In this way, on the one hand, the air permeability of the separator can be improved by the nanoscale ordered pores in the polymer nanosheet, and on the other hand, the electrolyte can be adsorbed by the nanoscale ordered pores in the polymer nanosheet, thereby improving the electrolyte retention capacity of the separator.
[0048] In an optional embodiment, the specific surface area of the polymer nanosheet is BET, 200m 2 / g≤BET≤1100m 2 / g. For example, BET is 200m 2 / g、500m 2 / g、800m 2 / g or 1100m 2 / g. This is beneficial to increase the contact area with the electrolyte, thereby improving the electrolyte retention capacity of the diaphragm.
[0049] In an optional embodiment, after the polymer nanosheets are immersed in the electrolyte for 500 hours, the total concentration of metal ions M in the electrolyte is less than 0.1 ppm, indicating that the polymer nanosheets have good stability in the electrolyte, thereby reducing the risk of side reactions between the polymer nanosheets and the electrolyte, which is beneficial to extending the life of the electrolyte, and further beneficial to extending the life of the lithium-ion battery.
[0050] In an optional embodiment, the porosity of the diaphragm is 40% to 70%. For example, the porosity of the diaphragm is 40%, 45%, 50%, 55%, 60% or 70%. This is conducive to improving the air permeability of the diaphragm, thereby improving the ionic conductivity of the diaphragm.
[0051] In an optional embodiment, the air permeability of the separator at 25° C. is 100 s / 100 cc to 200 s / 100 cc. For example, the air permeability is 100 s / 100 cc, 150 s / 100 cc or 200 s / 100 cc. This is beneficial to improving the ionic conductivity of the separator.
[0052] In an optional embodiment, the thermal shrinkage rate of the separator at 130° C. is less than or equal to 1.0%. For example, the thermal shrinkage rate of the separator at 130° C. is 0.6%, 0.8% or 1.0%, which shows that the separator of the present application has a lower shrinkage rate.
[0053] In an optional embodiment, the thermal shrinkage rate of the diaphragm at 150°C is less than or equal to 1.4%. For example, the thermal shrinkage rate of the diaphragm at 130°C is 1.0%, 1.2% or 1.4%. It can be seen that the diaphragm of the present application has a lower shrinkage rate.
[0054] In an optional embodiment, the metal ion M includes at least one of a zirconium ion, an aluminum ion, a calcium ion and a titanium ion, and the organic ligand includes at least one of biphenyl dicarboxylic acid, trimesic acid and 1,3,5-tri(4-carboxyphenyl)benzene (i.e., H3BTB), 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene (i.e., TCBPB), 1,3,5-tri(3,5-dicarboxylate-p-biphenyl)benzene (i.e., H6TDBPB) and 1,3,5-tri(4-carboxyphenylethynyl)benzene (i.e., H3BTE).
[0055] The present application has no particular limitation on the base film, as long as it can be used as a base film for the diaphragm. For example, the base film includes but is not limited to a porous base film made of materials such as polypropylene and polyethylene.
[0056] The present application also provides a method for preparing a polymer nanosheet, comprising the following steps:
[0057] Step A, dissolving an organic ligand and a metal salt containing a metal ion M in a solvent to obtain a first solution;
[0058] Step B, adding formic acid and water to the first solution, and mixing to form a second solution, wherein the concentration of formic acid in the second solution is 0.1wt% to 2wt%, and the concentration of water in the second solution is 0.1wt% to 3wt%;
[0059] Step C, heating the second solution, filtering and collecting the white solid precipitate generated by the reaction after the reaction is completed, to obtain polymer nanosheets.
[0060] In step A, the mass ratio of the organic ligand to the metal salt is 1:2.5-4, the solvent can be an organic solvent, for example, including but not limited to N,N-dimethylformamide (DMF); the water can be pure water or deionized water.
[0061] In step B, by regulating the concentration of formic acid and water within the above range, the growth of crystals along a two-dimensional plane can be regulated. This is because: (1) formic acid will form specific complexes with metal ions M in the solution. These complexes can participate in the growth of crystals as growth units, thereby affecting the growth and extension of crystals in different dimensional directions; (2) the concentration of formic acid and water affects the interfacial energy between the crystal and the solution. For crystals growing in a two-dimensional direction, the interfacial energy between the sides and the solution is usually low, which makes it easier for the crystal to grow in this direction. In addition, the addition of formic acid increases the acidity of the solution, reduces the pH value, changes the charge state of the crystal surface, and further affects the interfacial energy between the crystal and the solution. Therefore, by regulating the concentration of formic acid and water within the above range, the interfacial energy of different crystal faces can be affected, thereby achieving selective growth of crystals and forming the two-dimensional structure of the present application, that is, the organic ligands and the metal ions M are self-assembled to form polymer nanosheets with a sheet-like morphology.
[0062] In step C, after the second solution is heated and cooled to room temperature, a white solid precipitate is generated in the second solution, and the solid precipitate is the polymer nanosheet. In order to improve the purity of the polymer nanosheet, the obtained solid precipitate can be washed, dried, etc., and then vacuum stored for later use.
[0063] The present application provides a method for preparing a polymer nanosheet, which enables an organic ligand and a metal ion M to form a polymer nanosheet with a sheet-like morphology through self-assembly. When the polymer nanosheet is applied to a polymer functional layer of a diaphragm, it can not only improve the high temperature resistance of the diaphragm, but also improve the electrolyte retention capacity of the diaphragm, thereby improving the energy efficiency of the lithium-ion battery while improving the safety performance of the lithium-ion battery.
[0064] In an optional embodiment, the heating temperature is 115°C to 125°C, and the heating time is 40h to 60h. For example, the heating temperature is 115°C, 120°C or 125°C, and the heating time is 40h, 50h or 60h. By regulating the heating temperature and heating time within the above range, it is beneficial to fully react the organic ligand with the metal salt, improve the reaction efficiency, increase the radial size of the polymer nanosheets, and improve the total yield.
[0065] In an optional embodiment, the organic ligand is selected from at least one of biphenyl dicarboxylic acid, trimesic acid, 1,3,5-tri(4-carboxyphenyl)benzene, 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene, 1,3,5-tri(3,5-dicarboxylate-p-biphenyl)benzene and 1,3,5-tri(4-carboxyphenylethynyl)benzene, and the metal salt is selected from at least one of zirconium chloride, aluminum chloride and calcium chloride.
[0066] The present application has no particular restrictions on the method for regulating the average thickness and / or average width of the polymer nanosheets, as long as the purpose of the present application can be achieved. For example, the average thickness and / or average width of the polymer nanosheets generally increases with the increase in the content of the organic ligand and / or metal ion M during the reaction process. Based on this, the average thickness and / or average width of the polymer nanosheets can be regulated by regulating the content of the organic ligand and / or metal ion M in the first solution.
[0067] The present application has no particular restrictions on the method for regulating the pore size of the ordered pores in the polymer nanosheets, as long as the purpose of the present application can be achieved. For example, the pore size of the ordered pores in the polymer nanosheets usually increases with the increase of the van der Waals radius of the organic ligand molecules during the reaction process. Based on this, the pore size of the ordered pores in the polymer nanosheets can be regulated by regulating and selecting different organic ligands and metal ions M.
[0068] The present application has no particular restrictions on the method for regulating the specific surface area of the polymer nanosheet, as long as the purpose of the present application can be achieved. For example, the specific surface area of the polymer nanosheet generally increases with the increase in the pore size of the ordered pores in the polymer nanosheet. Based on this, the specific surface area of the polymer nanosheet can be regulated by selecting different organic ligands.
[0069] The present application also provides a battery, comprising the separator described in any of the above embodiments.
[0070] The lithium-ion battery of the present application also includes a positive electrode sheet. The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet usually includes a positive current collector and a positive electrode material layer. The positive electrode material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive current collector, that is, the positive electrode material layer can be arranged in a partial area of one surface of the positive current collector, or in the entire area of one surface of the positive current collector. In the present application, there is no special restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.
[0071] In the present application, the positive electrode active material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, it may include at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide and lithium iron manganese phosphate.
[0072] In the present application, the positive electrode active material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of fluorine-containing resins, polypropylene resins, fiber-type binders, rubber-type binders or polyimide-type binders.
[0073] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of one surface of the negative electrode collector, or in the entire area of one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.
[0074] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.
[0075] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.
[0076] The present application has no particular restrictions on the base film of the diaphragm, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the base film is a non-woven fabric, film or composite film with a porous structure, and the material of the base film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected. The present application has no particular restrictions on the thickness of the base film, as long as the purpose of the present application can be achieved. Exemplarily, the thickness of the base film is 5μm to 20μm.
[0077] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, after mixing at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) according to a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, add lithium salt to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.
[0078] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.
[0079] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.
[0080] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.
[0081] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.
[0082] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0083] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.
[0084] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0085] See also Figure 4 , Figure 4 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.
[0086] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.
[0087] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0088] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.
[0089] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.
[0090] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.
[0091] The diaphragm and the preparation method thereof of the present application are further described below in conjunction with more specific embodiments.
[0092] Example
[0093] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.
[0094] Example 1
[0095] <Preparation of Separator>
[0096] <Preparation of polymer nanosheets>
[0097] 12.5g of organic ligand 1,3,5-tri(4-carboxyphenyl)benzene (H3BTB) and 10.2g of metal salt zirconium chloride (ZrCl4) were dissolved in 4740g of DMF and stirred rapidly for 20min until all solids were dissolved to obtain a first solution; then 15g of formic acid and 60g of water were added to the first solution and stirred continuously to form a second solution, wherein the concentration of formic acid in the second solution was 0.3wt% and the concentration of water in the second solution was 1.2wt%; the second solution was transferred to a stainless steel reactor for sealed heating at 120°C for 48h, then cooled to room temperature, the white solid precipitate was collected by filtration, then washed with DMF and ethanol in turn, and then placed in a 120°C oven for vacuum drying for 24h to obtain polymer nanosheets.
[0098] <Preparation of polymer functional layer slurry>
[0099] Polymethyl methacrylate (PMMA) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 3:1 to obtain a mixture, and then the mixture is added to N-methylpyrrolidone (NMP) to prepare a dispersion with a concentration of 60g / L to 120g / L; the prepared polymer nanosheets are slowly added to the above dispersion and stirred evenly to obtain a polymer functional layer slurry.
[0100] <Preparation of polymer functional layer>
[0101] The polymer functional layer slurry is sprayed onto one side of the base film by a spray gun type spraying device, and after drying at 90°C, a diaphragm with a polymer functional layer is obtained, which is cut and set aside for use. The base film is a polyethylene (PE) porous film with a thickness of 9 μm, and the thickness of the polymer functional layer is 1 μm.
[0102] <Preparation of positive electrode sheet>
[0103] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 97:1:2; then N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly to prepare a positive electrode slurry with a solid content of 60wt%, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 11μm, and dried at 85℃, and then the above steps are repeated on the other surface of the positive electrode sheet, and a positive electrode sheet coated with a positive electrode material layer on both sides is obtained after rolling. The single-sided thickness of the positive electrode material layer is 100μm.
[0104] <Preparation of negative electrode sheet>
[0105] The negative electrode materials artificial graphite, conductive carbon black (Super-P) and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 96:1.5:2.5, deionized water was added, stirred evenly, and a negative electrode slurry with a solid content of 60wt% was prepared. Then the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, dried at 105℃, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode material layer coated on both sides was obtained, and the single-side thickness of the negative electrode material layer was 70μm.
[0106] <Preparation of Electrolyte>
[0107] Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1, dissolved, and fully stirred, and then placed in an environment of 5°C or less for 12 hours, and then lithium hexafluorophosphate (LiPF6) is added and mixed evenly to obtain an electrolyte. The molar concentration of LiPF6 in the electrolyte is 1.0 mol / L.
[0108] <Preparation of lithium-ion batteries>
[0109] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode and the negative electrode to play a role of isolation, and the side of the separator with the polymer functional layer faces the positive electrode sheet, and wound to obtain a bare battery cell. The bare battery cell is placed in an aluminum-plastic film packaging bag, vacuum dried, and then injected with electrolyte. After vacuum packaging, standing, and formation, a lithium-ion battery with a capacity of 280Ah is obtained.
[0110] Embodiment 2 to Embodiment 5
[0111] Except that the thickness of the polymer functional layer was adjusted according to Table 1 in <Preparation of Separator>, the rest was the same as Example 1.
[0112] Embodiment 6 to Embodiment 7
[0113] Except that in the preparation of the separator, the average thickness H and average width W of the polymer nanosheets are regulated by adjusting the amount of the organic ligand H3BTB and zirconium chloride added in the first solution, the rest is the same as Example 1. The average thickness H and average width W of the polymer nanosheets are shown in Table 2.
[0114] Example 8
[0115] The process is the same as Example 1 except that in the preparation of polymer nanosheets, the organic ligand H3BTB is replaced by trimesic acid, and the pore size of the ordered pores of the polymer nanosheets changes accordingly.
[0116] Example 9
[0117] The process is the same as Example 1 except that the organic ligand H3BTB is replaced by 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene in the preparation of polymer nanosheets, and the pore size of the ordered pores of the polymer nanosheets changes accordingly.
[0118] Comparative Example 1
[0119] The process is the same as that in Example 1 except that in <Preparation of Separator>, the polymer functional layer is not prepared on the surface of the base film, that is, the base film is directly used as the separator.
[0120] Comparative Example 2
[0121] Except that in <Preparation of diaphragm>, a 2 μm thick aluminum oxide (Al2O3) coating is applied on the surface of the base film, the rest is the same as Example 1.
[0122] Comparative Example 3 to Comparative Example 4
[0123] Except that the thickness of the polymer functional layer was adjusted according to Table 1 in <Preparation of Separator>, the rest was the same as Example 1.
[0124] Table 1 Preparation parameters of Examples 1 to 5 and Comparative Examples 1 to 4
[0125]
[0126] In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0127] Table 2 Preparation parameters of Example 1, Example 6 to Example 9
[0128]
[0129] Test methods and equipment
[0130] Thermal decomposition temperature test of polymer nanosheets:
[0131] The thermal decomposition temperature of the prepared polymer nanosheets was tested using a thermogravimetric analyzer (model: TGA55) in a test range of 25°C to 1000°C, a heating rate of 10°C / min, and a nitrogen atmosphere. The temperature at which the weight loss was 2.5% was taken as the decomposition temperature of the polymer nanosheets.
[0132] Polymer functional layer thickness test:
[0133] The test was carried out using a Mahr thickness gauge, and the test process was as follows: cut a base film and a diaphragm coated with a polymer functional layer into suitable sizes of 10 cm×10 cm, stack 10 layers of each, and put them into the Mahr thickness gauge to test the thickness. The measured value was divided by 10 to take the average value. The average thickness of the diaphragm was recorded as H1, and the average thickness of the base film was recorded as H0. Then the thickness of the polymer functional layer = H1-H0.
[0134] Diaphragm porosity test:
[0135] Place the diaphragm sample (size 10cm×10cm) in the sample chamber of the mercury intrusion instrument and seal it. Gradually increase the pressure, starting from low pressure, and record the volume of mercury entering the diaphragm pores at different pressures. Based on the mercury injection volume and pressure data, draw a pressure-mercury volume curve. The calculation formula is: Porosity = (V 孔 / V 总 )×100%, V 孔 is the pore volume obtained by mercury intrusion porosimetry, V 总 is the total volume of the diaphragm sample.
[0136] Diaphragm air permeability test:
[0137] According to the national standard GB / T1038-2000 "Plastic Film and Sheet Gas Permeability Test Method Pressure Difference Method", the time required for 100mL of air to pass through a 1 square inch diaphragm is tested under a pressure of 1.22kPa. The unit is s / 100cc. The shorter the time, the better the air permeability of the diaphragm.
[0138] Diaphragm thermal shrinkage test:
[0139] According to the national standard GB / T 13519-2016 "Polyethylene heat shrinkable film for packaging", the heat shrinkage rate of the diaphragm was tested at 130°C and 150°C, respectively, and the placement time was 30 minutes. The heat shrinkage rate of the diaphragm was calculated according to the following formula:
[0140]
[0141] Where S0 is the area of the diaphragm before heating, and S is the area of the diaphragm after shrinkage due to heating.
[0142] Metal dissolution test:
[0143] 1 g of the prepared polymer nanosheet was taken and immersed in 100 mL of electrolyte (EC: DMC: LiPF6 = 1: 1: 0.2) and allowed to stand for 500 h. The electrolyte was taken and the total concentration of metal ions M in the electrolyte was tested.
[0144] Lithium-ion battery energy efficiency test:
[0145] 0.5P / 0.5P energy efficiency test: At 25°C, the lithium-ion battery is charged and discharged in a cycle at 0.5P with a charge cut-off voltage of 3.7V and a discharge cut-off voltage of 2.45V until the capacity of the lithium-ion battery reaches 60% of the initial capacity.
[0146] 1P / 1P energy efficiency test: At 25°C, the lithium-ion battery is charged and discharged in a 1P charge and 1P discharge cycle, with a charge cut-off voltage of 3.7V and a discharge cut-off voltage of 2.45V, until the capacity of the lithium-ion battery reaches 60% of the initial capacity.
[0147] The energy efficiency of the lithium-ion battery after 500 cycles was tested by constant current method, where energy efficiency = 500th cycle discharge energy / 500th cycle charge energy × 100%.
[0148] Overcharge performance test:
[0149] According to the national standard "GB / T36276-2023 Overcharge Performance Test Method": 1) Initialize the charge of the lithium-ion battery and connect the voltage and temperature data acquisition lines; 2) Charge at a rated current (157A) until the voltage reaches 1.5 times the battery cell charging cut-off voltage or the time reaches 1h, stop charging, observe for 1h, and record the current, time, voltage, temperature and other parameters; 3) Record the experimental phenomena, including expansion, leakage, smoking, fire, explosion, rupture, etc. If one of the above experimental phenomena occurs, it is determined that thermal runaway has occurred.
[0150] Table 3 Performance data of each embodiment and comparative example
[0151]
[0152]
[0153] Combined with Table 3, it can be seen from Examples 1 to 5 and Comparative Examples 1 to 4 that although the 0.5P / 0.5P energy efficiency and 1P / 1P energy efficiency of Comparative Example 1 are relatively high, thermal runaway occurs in it, and the maximum overcharge temperature reaches 305°C, indicating that its diaphragm has failed at high temperatures and has potential safety hazards; although thermal runaway does not occur in Comparative Example 2, its 0.5P / 0.5P energy efficiency and 1P / 1P energy efficiency are relatively low, which is not conducive to reducing the operating cost of energy storage equipment; when the thickness of the polymer functional layer is too small (for example, Comparative Example 3), thermal runaway occurs in the lithium-ion battery, and the maximum overcharge temperature reaches 295°C, indicating that The diaphragm of the battery has failed at high temperatures, posing a safety hazard; when the thickness of the polymer functional layer is too large (for example, Comparative Example 4), although the lithium-ion battery does not experience thermal runaway, its 0.5P / 0.5P energy efficiency and 1P / 1P energy efficiency are still low, which is not conducive to reducing the operating cost of the energy storage device; while the lithium-ion battery of the present application has improved 0.5P / 0.5P energy efficiency and 1P / 1P energy efficiency without thermal runaway, thereby improving the energy efficiency of the lithium-ion battery while improving the safety performance of the lithium-ion battery, and is therefore more suitable for use in energy storage devices with high requirements for safety performance and operating costs.
[0154] Parameters such as the average thickness H, average width W, ordered pore diameter, and specific surface area of the polymer nanosheets usually also affect the performance of the diaphragm, thereby affecting the performance of the lithium-ion battery. From Examples 1 and 6 to 9, it can be seen that on the basis of the diaphragm of the lithium-ion battery having the polymer functional layer of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a lithium-ion battery with high safety performance and high energy efficiency.
[0155] Figure 5This is a SEM image of the polymer nanosheet prepared in Example 1 of the present application. It can be seen from the image that the polymer nanosheet has a relatively regular hexagonal crystal morphology, a sheet-like structure, and a width of about 900 nm.
[0156] The polymer nanosheets prepared in Example 1 were subjected to a metal dissolution test. After immersion for 500 hours, the total concentration of metal ions M in the electrolyte was measured to be 0.08 ppm, indicating that the polymer nanosheets had good stability in the electrolyte.
[0157] The above is a detailed introduction to a diaphragm, a method for preparing a polymer nanosheet, a battery and an energy storage device disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A diaphragm, characterized in that: include: A base film and a polymer functional layer, wherein the polymer functional layer is disposed on at least one side surface of the base film; The polymer functional layer comprises polymer nanosheets, which are sheet-like nanomaterials with ordered pores formed by the coordination of metal ions M and organic ligands; The thermal decomposition temperature of the polymer nanosheet is 400°C to 550°C.
2. The diaphragm according to claim 1, characterized in that The thickness of the polymer functional layer is 1 μm to 2 μm.
3. The diaphragm according to claim 1 or 2, characterized in that: The average thickness of the polymer nanosheet is H, the average width of the polymer nanosheet is W, 50nm≤H≤200nm, 0.3μm≤W≤1μm.
4. The diaphragm according to claim 3, characterized in that The pore size of the ordered pores in the polymer nanosheet is d, 5nm≤d≤50nm.
5. The diaphragm according to claim 3, characterized in that The specific surface area of the polymer nanosheet is BET, 200 m 2 / g≤BET≤1100m 2 / g.
6. The diaphragm according to claim 3, characterized in that After the polymer nanosheets are immersed in the electrolyte for 500 hours, the total concentration of metal ions M in the electrolyte is less than 0.1 ppm.
7. The diaphragm according to claim 1, characterized in that The diaphragm satisfies at least one of the following characteristics: a) the porosity of the diaphragm is 40% to 70%; b) the air permeability of the diaphragm at 25° C. is 100 s / 100 cc to 200 s / 100 cc; c) the thermal shrinkage of the diaphragm at 130° C. is less than or equal to 1.0%; d) The thermal shrinkage rate of the separator at 150° C. is less than or equal to 1.4%.
8. The diaphragm according to claim 1, characterized in that The metal ion M includes at least one of zirconium ion, aluminum ion, calcium ion and titanium ion, and the organic ligand includes at least one of biphenyl dicarboxylic acid, trimesic acid, 1,3,5-tri(4-carboxyphenyl)benzene, 1,3,5-tri(4′-carboxy[1,1′-biphenyl]-4-yl)benzene, 1,3,5-tri(3,5-dicarboxylate-p-biphenyl)benzene and 1,3,5-tri(4-carboxyphenylethynyl)benzene.
9. A method for preparing a polymer nanosheet, characterized in that: The following steps are involved: dissolving an organic ligand and a metal salt containing a metal ion M in a solvent to obtain a first solution; Adding formic acid and water to the first solution, and mixing to form a second solution, wherein the concentration of formic acid in the second solution is 1.5wt% to 2.5wt%, and the concentration of water in the second solution is 0.3wt% to 0.8wt%; The second solution is heated, and after the reaction is completed, the white solid precipitate generated by the reaction is filtered and collected to obtain the polymer nanosheet.
10. The preparation method according to claim 9, characterized in that: The heating temperature is 115°C to 125°C, and the heating time is 40h to 60h.
11. The preparation method according to claim 9, characterized in that: The organic ligand is selected from at least one of diphenyl dicarboxylic acid, trimesic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,3,5-tris(4′-carboxy[1,1′-biphenyl]-4-yl)benzene, 1,3,5-tris(3,5-dicarboxylate-p-biphenyl)benzene and 1,3,5-tris(4-carboxyphenylethynyl)benzene, and the metal salt is selected from at least one of zirconium chloride, aluminum chloride and calcium chloride.
12. A battery, characterized in that: A diaphragm comprising the diaphragm according to any one of claims 1 to 8.
13. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 12, wherein the battery is accommodated in the casing.
14. An electrical device, characterized in that: It includes the energy storage device as described in claim 13, and the energy storage device supplies power to the electrical equipment.